(untitled) (Acta Scientiarum. Animal Sciences, 2019)
The objective of this study was to investigate the effects of alpha-amylase supplementation on performance and carcass and cuts yield in broilers during finishing phase (21 to 42 days). A completely randomized experimental design with six treatments and eight replications was used: Positive Control (PC): no enzyme; Negative control (NC): without enzyme formulated with 6.34% less energy (- 6.34% ME); NC1: with 250 g ton-1 of alpha-amylase; NC2: with 500 g ton-1 of alpha-amylase; NC3: with 750 g ton-1 of alpha-amylase; NC4: with 1000 g ton-1 of alpha-amylase. Significant differences in weight gain, feed intake and feed conversion were reported with the inclusion of alpha-amylase. The NC treatment with inclusion of amylase provided improvement values of weight gain, feed conversion and feed intake, but do not was similarly in comparison to those obtained in broilers fed a diet that completely met the requirements during this phase. There was no dietary influence on carcass parameters. The use of alpha-amylase was effective in improving performance in broilers fed a diet of 200 kcal kg-1 of reduced metabolizable energy.